1998
DOI: 10.1172/jci1258
|View full text |Cite
|
Sign up to set email alerts
|

Direct evidence that protein kinase C plays an essential role in the development of late preconditioning against myocardial stunning in conscious rabbits and that epsilon is the isoform involved.

Abstract: Brief ischemic episodes confer marked protection against myocardial stunning 1-3 d later (late preconditioning [PC] against stunning). The mechanism of this powerful protective effect is poorly understood. Although protein kinase C (PKC) has been implicated in PC against infarction, it is unknown whether it triggers late PC against stunning. In addition, the entire PKC hypothesis of ischemic PC remains controversial, possibly because the effects of PKC inhibitors on PC protection have not been correlated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
181
0
5

Year Published

2000
2000
2007
2007

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(207 citation statements)
references
References 49 publications
20
181
0
5
Order By: Relevance
“…18 kDa protein. In contrast, the PKCε translocation inhibitor inhibited the in vitro 32 P labelling of the approx. 18 kDa protein by 79 + − 15 % (n = 3, P < 0.05).…”
Section: Introduction Of a Pkcε-selective Translocation Inhibitor Intmentioning
confidence: 82%
See 1 more Smart Citation
“…18 kDa protein. In contrast, the PKCε translocation inhibitor inhibited the in vitro 32 P labelling of the approx. 18 kDa protein by 79 + − 15 % (n = 3, P < 0.05).…”
Section: Introduction Of a Pkcε-selective Translocation Inhibitor Intmentioning
confidence: 82%
“…Ping et al [31] have established that induction of the early or late phases of PC in conscious rabbits triggered the translocation of the PKCε and PKCη isoenzymes to the cardiac particulate fraction. Qiu et al [32] found that differential inhibition of PKCη, but not PKCε, translocation by low concentrations of the PKC inhibitor chelerythrine allowed the recovery of systolic ventricular wall thickening in rabbits, while elevated concentrations of chelerythrine blocked PKCε translocation and PC. This same group demonstrated that nitric oxide was responsible for PC-induced PKCε activation and protection in rabbits [28] by a mechanism involving nitric oxideinduced nitration of PKCε and enhanced PKCε interaction with its intracellular RACK [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, activation of PKC after ischemic PC is isoform selective. Notably, the epsilon isoform appears to be responsible for the development of delayed cardioprotection in the rabbit [28]. Thus assessment of the PKC isoform relevant to protection induced by IH should be of interest.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have particularly focussed attention on the ␤-isoforms because of their potential role in cardiovascular dysfunction, especially as relates to endothelial cells and cardiac myocytes (45)(46)(47)(48)(49)(50)(51)(52)(53). Most studies analyzing PKC␤ isoforms have relied on inhibitors that show apparent specificity for ␤I/␤II versus other members of the PKC family (44, 45, 54 -59).…”
Section: Discussionmentioning
confidence: 99%